Cesium acetate-assisted crystallization for high-performance inverted CsPbI3 perovskite solar cells. (10th September 2022) - Li, Tiantian; Wu, Yue; Liu, Zhou; Yang, Yuanbo; Luo, Haowen; Li, Ludong; Chen, Peng; Gao, Xueping; Tan, Hairen
Abstract: Efficient inverted (p–i–n) type CsPbI3 perovskite solar cells (PSCs) have revealed promising applications due to their excellent thermal and photostability. Regulating the nucleation and crystallization of perovskite film is an important route to improving the performance of CsPbI3 PSCs. Herein, we explored cesium acetate (CsAc) as additive to manipulate the crystallization process of CsPbI3 perovskite films. By involving in the intermediate phase DMA1- x Cs x PbI3- y Ac y of perovskite, the pseudo-halide acetate (Ac − ) can retard the ion exchange reaction between DMA + and Cs +, leading to a perovskite with dense morphology, low defect density, and a long carrier lifetime. As a result, the optimal CsPbI3 PSCs yielded a high power conversion efficiency of 18.3%. Moreover, the encapsulated devices showed excellent operational stability and the devices retained their initial performance following 500 h of operation at the maximum power point under one-sun illumination in ambient conditions.